Effect of methanol leaf extract of Dalbergia saxatilis Hook.f (fabaceae) on renal function - Fatima Ismail Hassan; Abdulkadir Umar Zezi; Umar Habib Danmalam; Abdullahi Hamza Yaro (Mashhad University of Medical Sciences, 2016)
Objective: Dalbegia saxatilis (D.saxatilis) is used as a decoction in traditional medicine for ailments such as cough, small pox, skin lesions, bronchial ailments and toothache. This study is aimed at evaluating the toxic effect of methanol leaf extract of D.saxatilis on renal function. Materials and Methods: Wistar rats of both sexes were divided into four groups of five: control animals (group 1) received distilled water 1 ml/kg while groups 2, 3 and 4 were given graded doses of the extract (250, 500 and 1000 mg/kg body weight, respectively) daily for 28 days. Body weight changes were estimated by weighing the rats twice weekly using digital weighing balance. After 28 days, blood samples were obtained for evaluation of renal indices and the kidney was used for histopathology. Data were analysed using one-way and repeated measures ANOVA using SPSS version 20. Results: Significant weight increase in all groups were observed (p